IMPROVING THE EFFICIENCY OF BOXERS' TRAINING (Modern education and development, 2025)
Physical education and sports all types of people health storage and reinforcement for important tool become service does. Sports and physical education – youth generation of people physical-moral, spiritual - spiritual adjectives develop principles national-historical to roots has was power as national customs, traditions, values, people pedagogy and the East of thinkers in his works own expression found. Therefore in our country democratic changes further deepening and citizenship society foundations formation intensive step with going current in the period youth spiritually - educational , physical - moral in terms of perfection to deliver problem priority task as indicated.